Livestock Rendered: Animal Painting, Meatpacking and the Founding Collection of the Frye Art Museum - Kathleen Chapman (European Journal of American Studies)
This paper explores contradictions surrounding animal paintings in the Founding Collection of Seattle’s Frye Art Museum. The collection, assembled by Charles and Emma Frye, who settled in Seattle in the late 1800s, features nineteenth- and early-twentieth-century paintings by European artists, and includes numerous images of farm animals in agrarian settings in which any evidence of modern agricultural advances is absent and idyllic depictions of close, peaceful bonds between humans and domesticated animals predominate. Such calm, anachronistic scenes contrast starkly with the source of wealth that funded the Fryes’ acquisitions—meatpacking. While such imagery can be understood as concealing or deflecting attention from the bloody realities that funded the collection, it may also be regarded as offering hints of what less-exploitative relationships with animals can be. By focusing on painted renderings of domesticated animals’ labor and communicative capacities, I argue these seemingly innocuous, nostalgic images contain potential to move viewers to rethink today’s instrumentalized relationships with animals.